2019
DOI: 10.1186/s12882-019-1458-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations and phenotype in the steroid resistant nephrotic syndrome gene NUP93: a case report

Abstract: Background Monogenic mutations may be a significant cause of steroid-resistant nephrotic syndrome. NUP93 is a gene previously reported to cause isolated steroid-resistant nephrotic syndrome. Case presentation Here we describe a case of recessive, syndromic, steroid-resistant nephrotic syndrome caused by NUP93 mutation. Conclusions NUP93 may convey a phenotype that has not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…Phenotypes are listed in Table 2 and compare with previously-reported cases [10,11,[21][22][23][24]. All had multi-drug resistant focal segmental glomerulosclerosis (FSGS), progressing rapidly to CKD stage 5 within 2-12 months and required kidney transplant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypes are listed in Table 2 and compare with previously-reported cases [10,11,[21][22][23][24]. All had multi-drug resistant focal segmental glomerulosclerosis (FSGS), progressing rapidly to CKD stage 5 within 2-12 months and required kidney transplant.…”
Section: Resultsmentioning
confidence: 99%
“…Sandokji et al recently reported a 5-year-old girl presenting with SRNS, cardiomyopathy and developmental delay with autistic features. After kidney transplant, she had self-limiting proteinuria which resolved within a week [24] Nucleoporins are known to have a role in the immune system. Although there is no corresponding NUP93 mouse model, NUP210 knockout mice develop peripheral T-cell alterations [44] while NUP96 + / − animals present selective alterations of the immune system [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with the common observation of less likelihood of disease recurrence post‐transplant in vast majority of patients with SRNS due to inherited gene mutations 1 . Sandokji et al reported a 5‐year‐old non‐consanguineous female of African American and Hispanic origin with NUP93 variant resulting in ESRD and renal transplant with no recurrence 9 …”
Section: Discussionmentioning
confidence: 79%
“… 1 Sandokji et al reported a 5‐year‐old non‐consanguineous female of African American and Hispanic origin with NUP93 variant resulting in ESRD and renal transplant with no recurrence. 9 We identified a homozygous NUP93 novel sequence variant in a consanguineous Indian girl who had a rapidly progressive ESRD in the first decade of life with no disease recurrence in the post‐transplant period.…”
Section: Discussionmentioning
confidence: 98%